다중요소 기반의 내부 사용자 인증모델에 관한 연구 - 이재윤(Jae-yun Lee); 심호성(Ho-sung Shim); 한경석(Kyeong-Seok Han); 최용락(Yong-Lak Choi); 김종배(Jong-bae Kim) (한국정보통신학회논문지, 2015)
Financial information systems play such a pivotal role in the financial institution services that are provided for a large customers on the basis of various information including the personal information. As for the personal information collected during the transactions in the financial information systems, huge efforts and investment have been made to protect previously them from being inappropriately misused or illegally used if they could be released. Unfortunately, the frequent accidents on the leakage of sensitive personal information have occurred recently not only by external service users but even by internal system users. Therefore, the aim of this study is to suggest a model of advanced two-channel authentication for internal users in order to increase the stability of financial information systems with enhanced security. 금융정보시스템은 다수의 거래고객과 다양한 정보를 기반으로 서비스를 제공하는 특징이 있다. 금융관련 고객 정보는 유출시 불법적인 목적으로 사용될 수 있어, 이를 사전에 방지하고자 많은 투자와 노력을 기울인다. 고객 정보 유출은 외부 서비스 이용자에 의한 유출은 물론 내부 정보시스템 사용자에 의해서도 빈번히 발생하고 있다. 이에 본 연구에서는 2채널을 이용한 강화된 내부 사용자 인증모델을 제시하여 금융정보시스템의 안정적 운영을 도모하고자 한다.